Seasonality in oestrus and litter size in an assistance dog breeding colony in the United Kingdom - Wigham, Eleanor E.; Moxon, Rachel; England, Gary C.W.; Wood, James L.N.; Morters, Michelle K. (BMJ Publishing Group, 2017)
Evidence of seasonality in oestrus in bitches within specialist breeding programmes, such as those for assistance dogs, may support colony management through tailoring the distribution of resources required for breeding throughout the year. However, at present there are conflicting data regarding seasonality in oestrus (and litter size) in domestic dogs. The primary objective of this study was to investigate seasonal variations in oestrus and litter size in a large assistance dog breeding colony in the UK in order to optimise colony management. The authors analysed the annual distribution of 3624 observations of oestrus collected from 568 brood bitches from January 2005 to June 2014. The authors also evaluated the relationship between month and litter size for 1609 litters observed during the same period. There was no evidence of regular seasonal variations in oestrus or litter size by meteorological season or month. The lack of seasonality in oestrus may be a function of dogs in the UK, particularly valuable breeding bitches, being exposed to fairly constant environmental conditions throughout the year as a consequence of artificial light and heating during the winter months. The authors’ findings suggest that special consideration of the annual distribution of oestrus and litter size is unnecessary for the management of assistance dog breeding colonies similar to those in the UK.